The redefinition of criminal medical negligence according to the IAPCI draft proposals: Criminal negligence = violation of the duty of care + significant deviation from the standard of care + unreasonable risk + concrete possibility to comply with the sta (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This paper deals with two draft articles drawn up by the Subgroup of the Italian Association of Professors of Criminal Law (IAPCL/AIPDP) in charge of writing a proposal for a new liability regime for criminal negligence of health professionals. Before turning to the analysis of the drafts, the author highlights the main reasons why the legislator should abandon the current regulatory model (art. 590-sexies of the Criminal code). Concluding remarks tackle the path undertaken towards the redefinition of special statutes of criminal negligence within the Italian criminal doctrine.
Keywords: Italian Association of Professors of Criminal Law; Medical malpractice; Gross Negligence; Unzumutbarkeit; Penal Reform